Media Biji Jagung: Inovasi Pembelajaran Operasi Hitung Penjumlahan dan Pengurangan di Kelas 2 SD Negeri 02 Sokosari - Winda Restalia; Umi Mahmudah (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This qualitative study aims to analyze the implementation of corn seed media as an innovation in learning addition and subtraction arithmetic operations in Class 2 of SD Negeri 02 Sokosari. This study uses a case study approach with data collection techniques through participatory observation, in-depth interviews with teachers and students, and analysis of learning documents. The results of the study indicate that corn seed media is effective in improving students' conceptual understanding, especially for students with kinesthetic learning styles. The learning process goes through three main phases: introduction, operational, and evaluation, with 75% of students showing significant improvement in solving math problems. The findings also reveal that this media acts as a scaffolding that facilitates the transition of understanding from the concrete to the abstract stage, in accordance with Bruner's theory. The main obstacles include time management and classroom cleanliness, while positive responses come from teachers and students who consider this media fun and easy to access. This study recommends further development with the DECO (Discover, Engage, Contextualize, Optimize) approach and the need for school policies that support the use of local resources in learning. The implications of the study emphasize the importance of context-based media to create meaningful mathematics learning in elementary schools.